(untitled) (Jurnal Luminous: Riset Ilmiah Pendidikan Fisika, 2025)
This study aims to determine the effect of implementing a cooperative learning model integrated with Huyula values assisted by animated video media on students’ learning outcomes in the concepts of work and simple machines. The research employed an experimental method using a One Group Pretest-Posttest Design. The population consisted of eighth-grade students at SMP Negeri 3 Kabila in the 2024/2025 academic year. Samples were selected randomly using the Cluster Random Sampling technique, involving two classes: VIIIA as the experimental class and VIIIB as the replication class. The research instrument was a learning outcome test, and the data were analyzed using descriptive and inferential statistics. Data analysis included normality testing, hypothesis testing, and N-gain analysis. The average learning outcomes of the experimental class were 77.08, while the replication class scored 76.86. Hypothesis testing results showed that H1 was accepted, indicating a significant difference before and after the implementation. The N-gain scores were 0.39 for the experimental class and 0.62 for the replication class, both falling within the medium category. Thus, the cooperative learning model integrated with Huyula values and supported by animated videos has proven effective in improving students’ learning outcomes on the topic of work and simple machines. Keywords: Cooperative Learning Model, Huyula Values, Animated Video, Learning Outcomes, Work and Simple Machines